PEMBERDAYAAN MASYARAKAT DALAM PENANGANAN KESEHATAN KORBAN BENCANA GEMPA CIANJUR JAWA BARAT - Abdurrasyid Abdurrasyid; Rian Adi Pamungkas; Budi Mulyana; Sri Teguh Rahayu; Evi Medina Oktavia (LPPM Universitas Bina Bangsa, 2024)
Earthquakes are genuine disasters that occur due to the movement of the earth's plates, causing vibrations and even shaking. One of the impacts that occurred from the earthquake disaster in Cianjur Regency was the health care for the victims. Community empowerment in health care needs to be carried out as an effort to speed up health care for disaster victims in Cianjur Regency. The method for implementing empowerment is through 5 stages; 1) preparatory stage; 2) assessment stage; 3) activity planning stages; 4) implementation stages; and 5) termination stage. Empowerment activities speed up the community in collecting information on problem conditions and handling them. Volunteer officers who are members of the empowerment team for handling disaster victims need to have special emergency skills, wound care, and survival and safety skills